Complicating the already complex? Readability scores in bladder exstrophy and its treatment - Haffar, Ahmad; Morrill, Christian; Garcia, Adelaide; Werner, Zachary; Crigger, Chad; Gearhart, John P. (Frontiers in Urology, 2022)
Purpose: Classic bladder exstrophy (CBE), is a complex congenital malformation affecting formation of the lower abdominal wall and bladder. This study evaluates the readability of common online resources regarding CBE and its treatment. We hypothesize that high levels of reading comprehension are reflected in these resources, which may not be suitable to the general population for understanding this condition. Methods: The search terms “bladder exstrophy” and “bladder exstrophy treatment” were reviewed on the Google search engine. The first 100 search results for each search query were collected. The readability of each webpage was assessed using a combination of four independent validated formulae: the Gunning-Fog index (GFI), SMOG grade (Simple Measure of Gobbledygook), Dale-Chall index (DCI), and the Flesch-Kincaid grade (FKG). Results: A total of 200 search results were examined using the two search queries, yielding 72 unique webpages that fit the inclusionary criteria. The mean readability scores across all websites were a GFI of 14.3, SMOG score of 10, DCI of 9.06, and a FKG of 11.6. These scores correlate to adjusted grade levels of college sophomore, 11th grade, college, and 11th grade respectively. There was no significant difference of readability between website categories across GFI (p = 0.32), SMOG (p = 0.38), DCI (p = 0.33), and FKG (p = 0.36). Conclusion: This study demonstrates that online health information regarding CBE and its treatment is written at least the 11th grade reading level or above. This highlights the necessity to simplify online resources pertaining to CBE.